2008
DOI: 10.1080/10599230802453604
|View full text |Cite
|
Sign up to set email alerts
|

Wal-Mart Korea: Challenges of Entering a Foreign Market

Abstract: Wal-Mart entered South Korea in late 1990s for its international expansion; however, IT had a major failure in this market and left Korea in 2005 as the American way of marketing did not translate well in Korea. Wal-Mart had critical shortfalls in enabling value exchange with the Korean consumers as the Korean consumers had significantly different taste and preferences compared to American consumers. Wal-Mart's Every Day Low Price (EDLP) strategy was not perceived to have the "value" in the minds of the Korean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 3 publications
0
29
0
2
Order By: Relevance
“…Owing to cultural and environmental differences, consumers in different countries may have different shopping experiences even in the same type of stores (Bianchi & Arnold, 2004;Kim & Jin, 2002). Research has shown that consumer taste and preferences and shopping habits of Japanese and South Koreans consumers are different from US consumers, and thus affected the performance of Mal-Mart and Carrefour in these markets (Aoyama, 2007;Choi, 2006;Coe & Lee, 2006;Jin & Kim, 2001;Kim, 2008).…”
Section: Normative Pillarmentioning
confidence: 99%
See 4 more Smart Citations
“…Owing to cultural and environmental differences, consumers in different countries may have different shopping experiences even in the same type of stores (Bianchi & Arnold, 2004;Kim & Jin, 2002). Research has shown that consumer taste and preferences and shopping habits of Japanese and South Koreans consumers are different from US consumers, and thus affected the performance of Mal-Mart and Carrefour in these markets (Aoyama, 2007;Choi, 2006;Coe & Lee, 2006;Jin & Kim, 2001;Kim, 2008).…”
Section: Normative Pillarmentioning
confidence: 99%
“…For instance, the Japanese consumer has been referred to us the "most difficult consumer to strategize, as they require high quality on everything, and are knowledgeable about products, service, quality and prices from around the world… They are extremely brand-conscious, and demand brand products even on groceries" (Nikkei Business, 2005, p. 130, cited in Aoyama, 2007. In addition, research has shown that Japanese and South Korean consumers are sensitivity to price, seasonal changes in food items, love new products, and consider freshness and convenient shopping location as extremely important, are willing to make frequents visits to the supermarkets, corner shops, and traditional wet-markets to buy in small quantities (Choi, 2006;Coe & Lee, 2006;Jin & Kim, 2003;Kim, 2008). Kim (2008) noted that Korean local retailers accommodate this preference for food product freshness by transplanting the traditional outdoor market into a convenient indoors format hypermarkets.…”
Section: Normative Pillarmentioning
confidence: 99%
See 3 more Smart Citations